PERKEBUNAN KELAPA DALAM DI DUSUN API-API 1970an – 1990an - M. Firdaus, Aurora Nandia Febrianti (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2018)
Abstract            The purpose of this research is to describe the growth and development of the coconut plantation sector in the Api-Api village which is an important economic sector for the society, especially for economic actors involved in economic activities. It also aims to explain the economic life of residents in the Api-Api village ranging from those who became farmers as well as owners, laborers, and toke as a result of the growing sector of the coconut plantation. The research used the history method, which has stages of research from heuristics, criticism, interpretation, and historiography that aims to achieve historical truth. The historical method is a set of systematic principles and rules for collecting historical sources effectively, critically assessing, and presenting systematically in the form of a written report            This research also use of a multidisciplinary theoretical approach by applying other social sciences concepts such as economics and sociology. The findings in the field show that the Coconut Dalam Plantation in the Api-Api village is a hereditary effort, continuously experiencing improvement and progress starting from the number and area of land, the number of farmers as well as the owners of coconut plantation, wage labor, and toke, various types of production coconut, and the widespread marketing area. Keywords: Plantation, Coconut Dalam, Progress, Api-Api Village